Fabrication of novel ZnS/ZnAl2S4 nanocomposite using a facile solvothermal route - Pilapong C. (2014)
Novel ZnS/ZnAl2S4 nanocomposites were successfully synthesized via a surfactant-free solvothermal method using propylene glycol as a solvent. This method is mild, convenient, cheap and effective. X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), and photoluminescene spectroscopy techniques were used to characterize the ZnS/ZnAl2S4 nanocomposites and the bare ZnS nanorods. The results show that the nanocomposites were built up from a zinc blend ZnS nanorod core and wurzite ZnAl2S4 shell. Due to the PL spectra, the presence of ZnAl2S4 shell on ZnS nanorod can dramatically change optical properties of the nanocomposites. In addition, the formation mechanism of the ZnS/ZnAl2S4 nanocomposites was also discussed. ©2010 IEEE.